Safe and secure transport and storage of radioactive materials - Sorenson, Ken B. (Amsterdam : Woodhead Publishing is an imprint of Elsevier, 2015)
Safe and Secure Transport and Storage of Radioactive Materials reviews best practice and emerging techniques in this area. The transport of radioactive materials is an essential operation in the nuclear industry, without which the generation of nuclear power would not be possible. Radioactive materials also often need to be stored pending use, treatment, or disposal. Given the nature of radioactive materials, it is paramount that transport and storage methods are both safe and secure. A vital guide for managers and general managers in the nuclear power and transport industries, this book co.
9 -- Radiation protection by shielding in packages for radioactive materials
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed July 29, 2015).
Elsevier
Keywords: Radioactive substances -- Safety regulations; Radioactive substances -- Transportation; BUSINESS & ECONOMICS / Infrastructure; SOCIAL SCIENCE / General; Radioactive substances -- Safety regulations; Radioactive substances -- Transportation; Radioactive substances -- Storage -- Congresses; Radioactive substances -- Transportation -- Congresses; Radioactive substances -- Transportation; Electronic books; Electronic books